The Oxford-Hachette French dictionary : (Oxford University Press, 2007)
Clearly organized and thorough, the 4th edition of this essential reference provides numerous aids to the user, including a detailed section containing correspondence samples for a wide variety of purposes, lists of common words and phrases, lists of false friends, and lists of irregular and regular verbs (all of these in both French and English). The dictionary itself is rich with information and a pleasure to access in its two-color format. Sample phrases for each meaning of the term are provided, with highlighting if the word is an idiom or phrasal verb. Frequent inset boxes discuss tricky aspects of different terms for non-native speakers, or list in detail the use of common terms. A preface discusses the French spelling reform and lists words affected.